2018
DOI: 10.1039/c8nj02777c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral activity of novel spirocyclic nucleosides

Abstract: A diverse range of spirocyclic nucleosides have been prepared from a common precursor and tested for their antiviral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…with several known antiviral compounds. [25,[28][29][30][31] Epoxide 17 can be also used for generating simple diolebased fragments like 32 (rotatable bonds 0, MW 198, HBA 3, HBD 2 and TPSA 49) absolutely conform to Ro3 criteria and ideal for FBDD projects. [32] While, the presence of the double bond in 17 is certainly interesting because allows an extra point of diversity (synthetic handle) and represent an interesting site for chemical optimizations and follow up, conversely this moiety may act as a site of metabolic liability and therefore not always suitable for medicinal chemistry purposes.…”
Section: Resultsmentioning
confidence: 99%
“…with several known antiviral compounds. [25,[28][29][30][31] Epoxide 17 can be also used for generating simple diolebased fragments like 32 (rotatable bonds 0, MW 198, HBA 3, HBD 2 and TPSA 49) absolutely conform to Ro3 criteria and ideal for FBDD projects. [32] While, the presence of the double bond in 17 is certainly interesting because allows an extra point of diversity (synthetic handle) and represent an interesting site for chemical optimizations and follow up, conversely this moiety may act as a site of metabolic liability and therefore not always suitable for medicinal chemistry purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Cobb et al [ 39 ] reported the synthesis of a library of spirocyclic nucleoside analogs tested for antivirial activity. A series of azido-alkyne 53 were treated under thermal conditions in toluene for 24 hto obtain the corresponding spirocyclic nucleoside analogs 54 via intramolecular 1,3-dipolar cycloaddition ( Scheme 11 ).…”
Section: Clicked Nucleosides and Nucleotidesmentioning
confidence: 99%
“…The capping process is an essential post-transcriptional step for viral RNA translation by host ribosomes an addition to it is role in distinguishing between self mRNA and host mRNA (63). The 2′-O methyltransferase (2′-O MTase) enzyme that is located in non-structural protein 16 (nsp16) is one of the multiple enzymes required for cap structure formation, this enzyme is usually conserved (64). Several studies indicated that small molecules such as S-adenosyl-l-homocysteine, sinefungin, and aurintricarboxylic acid (ATA) (65-67) can inhibit nsp16 activity for CoV by interfering the interaction between nsp16/ nsp10 and nsp16/ nsp14.…”
Section: Journal Of University Of Anbar For Pure Science (Juaps)mentioning
confidence: 99%